2003
DOI: 10.1128/jvi.77.17.9486-9501.2003
|View full text |Cite
|
Sign up to set email alerts
|

Monkey Rotavirus Binding to α2β1 Integrin Requires the α2 I Domain and Is Facilitated by the Homologous β1 Subunit

Abstract: Rotaviruses utilize integrins during virus-cell interactions that lead to infection. Cell binding and infectionby simian rotavirus SA11 were inhibited by antibodies (Abs) to the inserted (I) domain of the ␣2 integrin subunit. To determine directly which integrins or other proteins bind rotaviruses, cell surface proteins precipitated by rotaviruses were compared with those precipitated by anti-␣2␤1 Abs. Two proteins precipitated by SA11 and rhesus rotavirus RRV from MA104 and Caco-2 cells migrated indistinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 87 publications
3
41
0
1
Order By: Relevance
“…This is consistent with the D308 conservation we found here in integrin-using rotaviruses, the abrogation of nar mutant cellular binding by VP5* containing D308A reported previously (55), and the requirement for Asp in the DGEA peptide for inhibition of collagen binding to ␣2␤1 by DGEA (48). It also confirms and extends studies reported elsewhere, which demonstrated by deletion of the ␣2 I domain that this region is necessary for RRV and SA11 binding to human ␣2␤1 expressed on CHO cells (35). As we have shown here that the ␣2 I domain is both necessary and sufficient for VP5* binding to occur, structural studies of rotavirus-␣2␤1 interactions can now be focused on VP5* binding to the ␣2 I domain.…”
Section: Discussionsupporting
confidence: 71%
“…This is consistent with the D308 conservation we found here in integrin-using rotaviruses, the abrogation of nar mutant cellular binding by VP5* containing D308A reported previously (55), and the requirement for Asp in the DGEA peptide for inhibition of collagen binding to ␣2␤1 by DGEA (48). It also confirms and extends studies reported elsewhere, which demonstrated by deletion of the ␣2 I domain that this region is necessary for RRV and SA11 binding to human ␣2␤1 expressed on CHO cells (35). As we have shown here that the ␣2 I domain is both necessary and sufficient for VP5* binding to occur, structural studies of rotavirus-␣2␤1 interactions can now be focused on VP5* binding to the ␣2 I domain.…”
Section: Discussionsupporting
confidence: 71%
“…Expression of the ␣ 2 ␤ 1 -integrin conferred vulnerability to rotavirus infection, suggesting that this integrin served as a rotavirus receptor. Subsequent studies identified the integrins ␣ x ␤ 2 , ␣ v ␤ 3 , and ␣ 4 ␤ 1 as other surface proteins that play a role in rotavirus attachment (13,14,16,21). A survey of the cholangiocyte and hepatocyte cell surface using FACS analysis revealed that cholangiocytes uniquely expressed ␣ 2 ␤ 1 , providing a potential mechanistic basis for RRV tropism to cholangiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-surface expression of the integrins ␣ 2 ␤ 1 , ␣ 4 ␤ 1 , ␣ x ␤ 2 , and ␣ v ␤ 3 has been shown to play a role in the attachment and entry of rotaviruses into other cell lines (8,13,14,16,21). Flow cytometry was performed on the mCl and H2.35 cells to determine whether they express the integrin subunits ␣ 1 , ␣ 2 , ␣ 4 , ␣ v , ␣ x , ␤ 1 , ␤ 2 , or ␤ 3 .…”
Section: Cholangiocyte Vs Hepatocyte Cell-surface Expression Of Intementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the expression of a2b1 integrin is strongly reduced in breast cancer, and a2b1 downregulation correlates with increased cell invasion and metastasis and thus with poor prognosis (Zutter et al, 1998;Ramirez et al, 2011). a2b1 integrin also acts as a co-receptor for several pathogens, such as echovirus 1 (EV1), rotavirus and human cytomegalovirus (Bergelson et al, 1992;Londrigan et al, 2003;Feire et al, 2004;Fleming et al, 2011). Binding of EV1 induces clustering of inactive a2b1 and directs virus-bound a2 integrin to a calpain-dependent degradation pathway in multivesicular bodies (Rintanen et al, 2012;Karjalainen et al, 2008;Upla et al, 2004).…”
Section: Introductionmentioning
confidence: 99%